Linguistic rights and language preservation - Julca Guerrero, Félix (2003)
This article summarizes a group of considerations and the linguistic juridical reflections about the linguistic rights. General considerations are mentioned about the linguistic diversity in the world and Latín American, languages in contact and sociolinguistic relationships. Besides, we developed the topic of the rise of juridical and linguistic conscience world wide regarding languages extinction. Then, we put forward some basic theoretical notions on linguistic rights such as individual and community rights, objective and subjective rights, among others. In this section we deal with aspects related to tolerance and fostering in languages. Finally, as a conclusion, we present some reflections towards the protection, preservation and development of minority and subjected languages.